Compressible hollow microlasers in organoids for high-throughput and real-time mechanical screening - Fang, Guocheng (2024)
Mechanical stress within organoids is a pivotal indicator in disease modeling and pharmacokinetics, yet current tools lack the ability to rapidly and dynamically screen these mechanics. Here, we introduce biocompatible and compressible hollow microlasers that realize all-optical assessment of cellular stress within organoids. The laser spectroscopy yields identification of cellular deformation at the nanometer scale, corresponding to tens of pascals stress sensitivity. The compressibility enables the investigation of the isotropic component, which is the fundamental mechanics of multicellular models. By integrating with a microwell array, we demonstrate the high-throughput screening of mechanical cues in tumoroids, establishing a platform for mechano-responsive drug screening. Furthermore, we showcase the monitoring and mapping of dynamic contractile stress within human embryonic stem cell-derived cardiac organoids, revealing the internal mechanical inhomogeneity within a single organoid. This method eliminates time-consuming scanning and sample damage, providing insights into organoid mechanobiology.